Ergasilus turkayi n. sp. (Copepoda, Cyclopoida, Ergasilidae): a gill parasite of Serrasalmus hollandi Jégu, 2003 (Characiformes, Serrasalmidae) from the Paragua River, Bolivia - Marques,Taísa M. (2017)
Abstract A new parasitic copepod species, Ergasilus turkayi n. sp., found on the gills of the Holland’s piranha, Serrasalmus hollandi Jégu, 2003, in the Paragua River, Bolivia, is described based on 10 adult females. The new species presents a triangular-shaped cephalothorax, spinules on interpodal plates and aesthetascs on antennule - two aesthetascs on the sixth, and one aesthetasc plus two setae on the fifth segment. Additionally, the second abdominal somite of E. turkayi n. sp. bears an anal pseudoperculum, a dorsal and elongate projection which is usually absent or vestigial in poecilostome families within the Cyclopoida but that was never reported in species of Ergasilidae.